TOR signaling inhibition in intestinal stem and progenitor cells affects physiology and metabolism in Drosophila. - Strilbytska, O.M.; Storey, K.B.; Lushchak, O.V. (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2020)
In all eukaryotic organisms, the control of growth, metabolism, reproduction, and lifespan is realized by interactions of genetic and environmental signals. An important player in the regulatory network is the target of rapamycin (TOR) signaling pathway, which is triggered by nutritional cues. Given the pivotal role of TOR in regulating multiple processes in organisms, we inhibited TOR by inducible expression of specific RNAi in Drosophila intestinal stem and progenitor cells or progenitor cells alone. We found that TOR inhibition in stem and progenitor cells shortened the lifespan on both regular diet and under malnutrition. Moreover, flies became more short-lived under starvation or oxidative stress conditions if TOR was inhibited. TOR-RNAi expression resulted in a decrease in body glycogen and TAG levels. All these physiological and metabolic changes might be partially explained by significant changes in mRNA levels for genes encoding the Drosophila insulin-like peptides (dilp2, dilp3 and dilp5) with subsequent effects on insulin signaling to modulate gene expression in peripheral tissues (e.g. tobi and pepck transcripts). In the gut, a strong increase in transcript levels of cytokines upd2, upd3 and downstream target socs36e of the JAK/STAT signaling pathway in the gut indicate an important role for this signaling pathway when TOR is inhibited.